Sistem Monitoring Bukti Digital Untuk Meningkatkan Kontrol Terhadap Kasus Cybercrime Di Indonesia - Widatama, Krisna (INTEK : Jurnal Informatika dan Teknologi Informasi, 2019)
Nowadays, the computer technology is growing rapidly. This has a positive impact, many people can be helped by the computer. In addition, the types of jobs available are in-creasing. But, there are also negative impacts, for example the computer crimes are growing dramatically. The komputer crimes will be handled where the place of computer crime occurred at the District Level (POLSEK). The problem occurs is when police agen-cies at the District Level do not have tools to investigate digital evidence. So the proce-dure to handle this computer crime is send the physical evidence to the Regional Level (POLDA) to be acquired and analyzed. It will make the digital evidence vulnerable to be acquired and manipulated when the physical evidence is sent to the Regional Police Agency by people who do not have au-thority. It is necessary to renew the procedure for handling digital evidence in the case of a computer crime and integrated system between them. This study will produce a procedure for handling digital evidence through an integrated monitoring system between POLSEK and POLDA agencies. It is hoped that through this monitoring system, authenticity can be maintained and the digital evidence can be ac-cepted by judge in the court.